Analysis of Digital Marketing Techniques on the Instagram Application (Case Study of the @jajanserang Instagram Account) - Melati, Nyimas; Yuliana, Nina (Jurnal Sosial Sains dan Komunikasi, 2024)
Currently, Instagram has become one of the dominant platforms in digital marketing for building brands, by reaching a wider audience. General trends in marketing on Instagram include the use of creative content strategies, and optimizing the use of hashtags. One example of an Instagram account that is actively doing this is the @jajanserang account. With so many followers, the Instagram account @jajanserang stands out with interesting content and an effective marketing strategy that focuses on information about the culinary industry, food, cafés and tourist attractions in the city of Serang. This account has succeeded in attracting the audience's attention with a combination of tempting videos, interactions being active with followers, using the right hashtags, and intelligent adaptation to Instagram trends and algorithms make this account interesting to research. Apart from that, the aim of this research is to find out the techniques used in digital marketing on the Instagram account @jajanserang such as engagement rate, use of hashtags, and the type of content published are also keywords in the caption so that this account is liked by many people. The research approach applied in this research is qualitative using content analysis techniques by collecting the last 100 posts published by the @jajanserang account in the research period, namely (26/11/23) which were then categorized and analyzed. The results obtained in this research are that the @jajanserang account uses several digital marketing techniques, namely advertising, storytelling, use of hashtags, sales promotions, giveaways, comedy and audio music. Where advertising and sales promotions are the most effective techniques in attracting customers. Then hashtags are a technique that is used very often, while comedy and audio are the least common.